Thermal performance, usage behaviour and food waste of domestic refrigerators in a university student community - Galvão, Diogo Alexandre Sobreiro (2019)
Food safety and quality as well as storage conditions leading to food waste are related to the reduced thermal performance of domestic refrigerators, the mismanagement of food stored in it or the misuse of the equipment. This paper analyses the operative conditions of refrigerators in the student community of the University of Beira Interior (Covilhã, Portugal). A test sample of 51 appliances in the student households was instrumented with temperature dataloggers. Simultaneously, surveys on the use of refrigerator and food waste were applied to the students, ultimate users of the appliances. The students, with an average of 23 years old, mostly female (65.9%), live alone (6%), with their parents (24%), or with other students (71%). The test sample of appliances had, on average, a nominal electrical power of 126 W and an inner volume of 205 liters. It was found that the average storage temperature was 5.5ºC. The storage temperature in the appliances increased with the number of people who used it. This figure was largely due to improper use behaviour, in particular the number of times that the refrigerator door was open unnecessarily. The joint analysis of these data allows relating the use behaviour of with food waste. The comparison with similar studies conducted in the past shows that the average storage temperature in the current study is lower, mainly due to the technological evolution of appliances as well as the global awareness concerning food safety and food waste. The results of this work, apart from offering results about the performance of the operative conditions of refrigerators in a community not studied so far, highlights the need for further awareness of good practices to reduce food waste and simultaneously ensure food safety of the perishable food products stored in domestic refrigerators. These results could be extrapolated to the remaining people in order to develop strategies to improve cities sustainability.